The Boundedness of Generalized Fractional Integral Operators on Small Morrey Spaces - Syaifudin, Rizky Aziz; Karim, Corina; Marjono, Marjono; Rahman, Hairur (CAUCHY: Jurnal Matematika Murni dan Aplikasi, 2024)
The small Morrey space is the set of locally Lebesgue integrable functions with norm defined supremum over radius of ball . This paper aims to prove the boundedness properties of the generality of fractional integral operators in small Morrey spaces using Hedberg-type inequality.  The first, in this paper will be discuss to prove Hedberg-type inequality on small Morrey spaces using dyadic decomposition, H lder inequality, and doubling condition. Furthermore, by using the inequality, it can be proven that the boundedness of generalized fractional integral operators on small Morrey spaces.